2021
DOI: 10.1200/jco.20.02903
|View full text |Cite|
|
Sign up to set email alerts
|

Tipifarnib in Head and Neck Squamous Cell Carcinoma WithHRASMutations

Abstract: PURPOSE Mutations in the HRAS (m HRAS) proto-oncogene occur in 4%-8% of patients with recurrent and/or metastatic (R/M) head and neck squamous cell carcinoma (HNSCC). Tipifarnib is a farnesyltransferase inhibitor that disrupts HRAS function. We evaluated the efficacy of tipifarnib in patients with R/M m HRAS HNSCC. METHODS We enrolled 30 patients with R/M HNSCC in a single-arm, open-label phase II trial of tipifarnib for m HRAS malignancies; one additional patient was treated on an expanded access program. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(96 citation statements)
references
References 37 publications
1
95
0
Order By: Relevance
“…At this time, it is unclear if drugs targeting NRAS, HRAS, or KRAS (BI1701963 targeting KRAS and Tipifarnib targeting HRAS) will have any relevance for PTC in the future. Ho et al (30) reported stable disease in 9 of 11 HRAS-mutated thyroid cancer patients treated with Tipifarnib; however, they focus on head and neck squamous cell carcinoma in their report and the specific histology of the thyroid cancer patients is not included. Given the predominance of RAS mutations in RAI avid as opposed to RAI-refractory DTC reported in the literature (31), this pathway might be less relevant for the treatment of RAI-R disease.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, it is unclear if drugs targeting NRAS, HRAS, or KRAS (BI1701963 targeting KRAS and Tipifarnib targeting HRAS) will have any relevance for PTC in the future. Ho et al (30) reported stable disease in 9 of 11 HRAS-mutated thyroid cancer patients treated with Tipifarnib; however, they focus on head and neck squamous cell carcinoma in their report and the specific histology of the thyroid cancer patients is not included. Given the predominance of RAS mutations in RAI avid as opposed to RAI-refractory DTC reported in the literature (31), this pathway might be less relevant for the treatment of RAI-R disease.…”
Section: Discussionmentioning
confidence: 99%
“…A Structure of RAS proteins, including the effector lobe (aa 1-86), allosteric lobe (aa , and HVR (aa 167-188/189). Switch I (aa [30][31][32][33][34][35][36][37][38][39][40] and switch II (aa [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] are located in the effector lobe and function in effector binding and GEF or GAP binding. The HVR domain contributes to RAS binding to cell membranes.…”
Section: Ras Mutation Frequency and Hotspots In Human Cancersmentioning
confidence: 99%
“…However, FTase inhibitors (FTIs) exhibited disappointing results in clinical trials [114] toward to pancreatic cancer, which mainly possess KRAS mutation [65][66][67], and subsequent research revealed KRAS and NRAS gained alternative modifications by geranylgeranyltransferases (GGTase) in cells treated with FTIs [68]. Noteworthily, tipifarnib, a FTase inhibitor, exhibited encouraging efficiency in cancer harboring HRAS mutation [69,70]. Although simultaneous inactivation of FTase and GGTase exhibited tumorigenesis inhibition in mouse models [71,72], the toxicity associated with GGTIs limited their utility, thus reducing the benefit of targeting KRAS through combined FTase and GGTase inhibition [73].…”
Section: Targeting Upstream Proteinsmentioning
confidence: 99%
“…The activity of HRAS is synchronized by the enzyme farnesyltransferase. Tipifarnib inhibits this enzyme and results in decreasing HRAS expression and tumor growth diminished but until tipifarnib in trial phases [37][38][39]. Many therapies are in trial phases, some are in use but these therapies are not completely treating cancer.…”
Section: Cancer Stem Cell-targeted Therapiesmentioning
confidence: 99%